Participatory evaluation of delivery of animal health care services by community animal health workers in Karamoja region of Uganda - Bugeza, James; Kankya, Clovice; Muleme, James; Akandinda, Ann; Sserugga, Joseph; Nantima, Noelina; Okori, Edward; Odoch, Terence (PLoS ONE, 2017)
An evaluation exercise was carried out to assess the performance of Community Animal Health Workers (CAHWs) in the delivery of animal health care services in Karamoja region, identify capacity gaps and recommend remedial measures. Materials & methods Participatory methods were used to design data collection tools. Questionnaires were administered to 204 CAHWs, 215 farmers and 7 District Veterinary Officers (DVOs) to collect quantitative data. Seven DVOs and 1 Non Government Organization (NGO) representative were interviewed as key informants and one focus group discussion was conducted with a farmer group in Nakapiripirit to collect qualitative data. Questionnaire data was analyzed using SPSS version 19. Key messages from interviews and the focus group discussion were recorded in a notebook and reported verbatim. Results 70% of the farmers revealed that CAHWs are the most readily available animal health care service providers in their respective villages. CAHWs were instrumental in treatment of sick animals, disease surveillance, control of external parasites, animal production, vaccination, reporting, animal identification, and performing minor surgeries. Regarding their overall performance 88.8%(191/215) of the farmers said they were impressed. The main challenges faced by the CAHWs were inadequate facilitation, lack of tools and equipments, unwillingness of government to integrate them into the formal extension system, poor information flow, limited technical capacity to diagnose diseases, unwillingness of farmers to pay for services and sustainability issues. Conclusions and recommendations CAHWs remain the main source of animal health care services in Karamoja region and their services are largely satisfactory. The technical deficits identified require continuous capacity building programs, close supervision and technical backstopping. For sustainability of animal health care services in the region continuous training and strategic deployment of paraprofessionals that are formally recognised by the traditional civil service to gradually replace CAHWs is recommended.
Keywords: Participatory evaluation; Animal health care services; Community animal health workers; Karamoja region; Uganda